Perancangan Komunikasi Visual Web Games Interaktif “Gooclean.Com” Guna Menanamkan Budaya Anti Korupsi Sejak Dini - Andreas James Darmawan; Nunnun Bonafix (Bina Nusantara University, 2011)
Along with the increasing number of corruption, the role of visual communication is also increasingly necessary. Its role is as a maker of communications media that attract, encourage, and interactive. So the anti-corruption culture that wants implanted were well received and is embedded in the consciousness of the receiver behave. Article clarifies visual communication